Harnessing Regional Frameworks for Weather, Water, and Climate Services in Africa Key to Securing its Climate Future - Amha, Yosef; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
There is an urgent need for effective weather, water, and climate services (WWCS) to support informed decision-making and strengthen climate resilience across Africa. However, the existing WWCS landscape on the continent is highly fragmented regarding capacity and service coverage, with significant differences at the national level. Establishing Regional Frameworks for Weather, Water, and Climate Services (RFWWCS) allows one to fill such gaps and build coordinated efforts toward climate service provision. By enhancing the development, delivery, and application of timely, accurate, and context-specific climate information, RFWWCS can attain significant progress in sustainable development and climate resilience across Africa. The establishment of RFWWCS will involve, among others, planning and baseline assessments, reviewing the status of regional institutions, developing the RFWWCS framework, validating the regional action plan, and finally, putting the framework into operation. The steps above are foreseen to achieve coordination among regional institutions and guarantee an appropriate design for providing climate services to the NFWWWS at country levels. If it is executed correctly, the RFWWCS will increase coordination of the regional institutions in co-producing and communicating WWCS; governance and institutional arrangements through clarity in roles and responsibilities among the stakeholders; alignment with global, regional, and national initiatives on the long-term sustainability of climate services within various sectors; building on existing initiatives and infrastructure; integrating recent advances in technology for improved service delivery in areas such as Earth observation and artificial intelligence. Success in the RFWWCS would be realized through fundamental challenges posed by adequate weather and climate observations, enormous, underdeveloped access, and effective sharing of data together with forecasting skills. We would promote a regional climatic responsive service by grasping these opportunities and advancing with different stakeholders working in conjunction with one another. In addition, RFWWCS will be oriented toward cross-border climate risks and integrated into national and regional development plans through climate services to ensure that climate information underpins informed decision-making in agriculture, health, water, and disaster risk management. Furthermore, its operationalization requires strong political will, good governance, and reasonable financial support. A common and sustainable RFWWCS will generally enable African countries to respond more effectively towards climate variability and change while pursuing climate-resilient development across the continent.